MANAGEMENT OF ARCHIVIST RESOURCES AT THE GENERAL SECRETARIAT OF THE INDONESIAN NATIONAL POLICE - Sukma Juwita; Asropi Asropi (DIA: Jurnal Administrasi Publik, 2026)
This study aims to analyze the management of archivist resources at the General Secretariat of the Indonesian National Police (Polri), focusing on enhancing the competence and career development of archivists. Archivists play a vital role in maintaining the integrity and accountability of records as part of public administrative services. However, Polri is facing a crisis due to a shortage of competent archivists, exacerbated by the low interest among personnel and negative stigma associated with the archivist profession. Through a qualitative descriptive approach, this study identifies inhibiting factors and formulates development strategies for archivist resources based on a merit system. The findings indicate that training, competency certification, and regulations equivalent to other functional positions are essential to improving the professionalism and attractiveness of the archivist position within Polri.